Mechanism of action of the nucleotide-binding oligomerization domain-like receptor protein 3 inflammasome and its regulation in liver injury - Yifan Lu; Tianyu Wang; Bo Yu; Kang Xia; Jiayu Guo; Yiting Liu; Xiaoxiong Ma; Long Zhang; Jilin Zou; Zhongbao Chen; Jiangqiao Zhou; Tao Qiu; et al. (Chinese Medical Journal)
Abstract. Nucleotide-binding oligomerization domain (NOD)-like receptor protein 3 (NLRP3) is a cytosolic pattern recognition receptor that recognizes multiple pathogen-associated molecular patterns and damage-associated molecular patterns. It is a cytoplasmic immune factor that responds to cellular stress signals, and it is usually activated after infection or inflammation, forming an NLRP3 inflammasome to protect the body. Aberrant NLRP3 inflammasome activation is reportedly associated with some inflammatory diseases and metabolic diseases. Recently, there have been mounting indications that NLRP3 inflammasomes play an important role in liver injuries caused by a variety of diseases, specifically hepatic ischemia/reperfusion injury, hepatitis, and liver failure. Herein, we summarize new research pertaining to NLRP3 inflammasomes in hepatic injury, hepatitis, and liver failure. The review addresses the potential mechanisms of action of the NLRP3 inflammasome, and its regulation in these liver diseases.